Effects of Kaolin Clay on the Mechanical Properties of Asphaltic Concrete AC14 - M. E., Abdullah; Putra Jaya, Ramadhansyah; M. H., Rafsanjani; Norhidayah, Abdul Hassan; Haryati, Yaacob; Mohd Rosli, Hainin; Muhammad Naqiuddin, Mohd Warid; M. K. I., Mohd Satar; Md. Maniruzzaman, A. Aziz; A., Aziz; Nordiana, Mashros (IOP Science, 2018)
This study investigated the effect of kaolin clay on the mechanical properties of asphaltic concrete AC14 through Marshall Stability, resilient modulus, and dynamic creep tests. Four replacement levels of kaolin clay (2%, 4%, 6%, and 8% by weight of the binder) were considered. Kaolin clay functioned as an effective filler replacement material to increase the mechanical properties of asphalt mixtures. Asphaltic concrete with 2% to 4% kaolin clay replacement level exhibited excellent performance with good stability, resilient modulus, and creep stiffness.